2021
DOI: 10.1007/s00181-021-02162-9
|View full text |Cite
|
Sign up to set email alerts
|

Do methane emissions converge? Evidence from global panel data on production- and consumption-based emissions

Abstract: Methane emissions are the second most important contributor to global warming. Knowledge about the dynamics of methane emissions facilitates the formulation of climate policies and the understanding of their consequences. We investigate whether methane emissions released from production and embodied in consumption converge within and across regions. Our estimates rely on global panel data on methane per capita and methane intensities over 1997–2014. We find that emissions converge within countries. The short h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…, S < 0 (7) If Z > 0, it means that the XCH 4 concentration shows an increasing trend in this time series; otherwise, it is decreasing the trend, and the larger the absolute value, the more obvious the trend is [41].…”
Section: Mann-kendall (M-k) Nonparametric Testmentioning
confidence: 97%
See 1 more Smart Citation
“…, S < 0 (7) If Z > 0, it means that the XCH 4 concentration shows an increasing trend in this time series; otherwise, it is decreasing the trend, and the larger the absolute value, the more obvious the trend is [41].…”
Section: Mann-kendall (M-k) Nonparametric Testmentioning
confidence: 97%
“…The increase in methane concentration in the atmosphere in the industrial era is mainly due to human activities [5]. The main sources of atmospheric methane originate from the biological processes of the anaerobic environment; the atmospheric methane produced by abiotic processes accounts for only 20%, approximately [6,7], mainly including natural sources (wetlands, termites, etc.) and anthropogenic sources (coal mining leakage, paddy field emission, ruminant emission, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers had a broader focus on greenhouse gases, and methane and nitrous oxide became research hotspots. Methane is the second largest greenhouse gas [103,104], and its global warming potential exceeds that of carbon dioxide by 28 times [105]. The global warming potential of nitrous oxide on a 100-year time scale is 298 times that of carbon dioxide [106].…”
Section: Research Frontiersmentioning
confidence: 99%
“…Even though CO 2 has a longer-lasting effect, methane currently sets the pace for warming [4]. Recent studies confirmed that the atmospheric concentration of CH 4 reached an unprecedented level since records began, exhibiting an accelerating upward trend [5]. However, unlike CO 2 emissions, methane emissions have not been well understood in both developed and developing countries [6][7][8].…”
Section: Introductionmentioning
confidence: 99%